2006
DOI: 10.1021/jf052495n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Key Aroma Compounds in the Beverage Prepared from Darjeeling Black Tea:  Quantitative Differences between Tea Leaves and Infusion

Abstract: By application of the aroma extract dilution analysis on the volatile fraction isolated from a black tea infusion (Darjeeling Gold Selection), vanillin (vanilla-like), 4-hydroxy-2,5-dimethyl-3(2H)-furanone (caramel), 2-phenylethanol (flowery), and (E,E,Z)-2,4,6-nonatrienal (oat-flake-like) were identified with the highest flavor dilution (FD) factors among the 24 odor-active compounds detected in the FD factor range of 4-128. Quantitative measurements performed by means of stable isotope dilution assays and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
339
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(365 citation statements)
references
References 26 publications
21
339
4
1
Order By: Relevance
“…The results of each attribute were calculated as arithmetic mean. The assessors were trained immediately prior to analysis with aqueous odorant solutions in defined concentrations (factor 100 above the odour threshold) [24][25][26]. The odorant solutions reflected the evaluated characteristic odour attributes of the flours: buttery (butane-2,3-dione, 120 lg/L), cooked potato-like (3-(methylthio-) propanal, 140 lg/L), malty (3-methylbutanal, 120 lg/L), mouldy (geosmin, 2.1 lg/L), oat flakes-like [(E,E,Z)-nona-2, 4,6-trienal, 2,6 lg/L], pea-like (3-isobutyl-2-methoxypyrazine, 3.9 lg/L), popcorn-like, roasty (2-acetyl-1-pyrroline, 12 lg/L), vinegar-like (acetic acid, 18,000,000 lg/L), vomitlike and cheesy (butanoic acid, 120,000 lg/L).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The results of each attribute were calculated as arithmetic mean. The assessors were trained immediately prior to analysis with aqueous odorant solutions in defined concentrations (factor 100 above the odour threshold) [24][25][26]. The odorant solutions reflected the evaluated characteristic odour attributes of the flours: buttery (butane-2,3-dione, 120 lg/L), cooked potato-like (3-(methylthio-) propanal, 140 lg/L), malty (3-methylbutanal, 120 lg/L), mouldy (geosmin, 2.1 lg/L), oat flakes-like [(E,E,Z)-nona-2, 4,6-trienal, 2,6 lg/L], pea-like (3-isobutyl-2-methoxypyrazine, 3.9 lg/L), popcorn-like, roasty (2-acetyl-1-pyrroline, 12 lg/L), vinegar-like (acetic acid, 18,000,000 lg/L), vomitlike and cheesy (butanoic acid, 120,000 lg/L).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…1). It was reported that β-linalool and geraniol play important roles in the formation of black tea aroma (Schuh and Schieberle, 2006). β-Linalool and its corresponding oxides contribute vitally to the formation of the sweet aroma of black tea, whereas geraniol has an effect on the formation of the floral aroma of black tea.…”
Section: Differences Among Terpene Alcoholsmentioning
confidence: 99%
“…Part of the aroma concentrates could not be fully recovered during the distillation process, so we tried to quantify the amount by using the above-mentioned method. It is of interest from the results of this study that -damascenone, which is a well-known key odorant in rose, 12) wine 13) and black tea 14) was identified for the first time in Tahitian vanilla beans. 3-Methylnonane-2,4-dione was identified for the first time in vanilla beans, and phenylacetic acid was also identified for the first time in Tahitian vanilla beans.…”
Section: Aroma Profile Of Tahitian and Madagascar Vanilla Beansmentioning
confidence: 90%